Antipsychotic medication for behaviors that challenge in individuals with intellectual disabilities: a clinically informed review - Pascucci, Alessandro; Gerber, Fabienne; Besson, Marie; Kosel, Markus (Frontiers in Psychiatry, 2025)
Individuals with intellectual disabilities (ID) frequently exhibit behaviors that challenge (BC), such as aggression and self-injury, which significantly impact their quality of life. Pharmacological interventions, particularly antipsychotics, are regularly employed to manage these behaviors. However, these medications are frequently prescribed off-label, increasing the risks of polypharmacy, drug-drug interactions, and potential adverse effects. We conducted a comprehensive literature search to identify studies on antipsychotic interventions for BC in individuals with ID. Eligible studies included observational (cross-sectional and longitudinal) studies and randomized controlled trials (RCTs). Findings from RCTs were mixed: while some trials reported reductions in aggression and irritability with antipsychotics such as risperidone and olanzapine, others showed no advantage over placebo or supported deprescription strategies. Observational studies generally supported the short-term effectiveness of risperidone, olanzapine, and zuclopenthixol in reducing aggressive behaviors, although evidence for their impact on self-injurious behaviors (SIBs) was inconsistent. Across both study types, the use of antipsychotics was consistently associated with adverse effects, including sedation, weight gain, and metabolic changes. Preliminary open-label evidence suggested that aripiprazole may reduce BC in individuals with Fragile X Syndrome (FXS), while causing fewer metabolic side effects. These findings highlight key limitations of the current literature, including the scarcity of studies focusing specifically on ID populations, small sample sizes, the limited number of RCTs, and often controversial or inconsistent results. Despite these limitations, the review indicates potential benefits from reducing dosages and discontinuing long-term antipsychotic use, particularly when guided by personalized treatment plans and regular reassessment. Overall, the results support cautious and individualized prescribing, with close monitoring of adverse effects and attention to deprescribing when appropriate. Further longitudinal and naturalistic studies are warranted, along with the development of structured tools to assist clinicians in optimizing pharmacological care for this vulnerable population.